PENGARUH MINAT DAN KEMANDIRIAN BELAJAR SISWA TERHADAP PRESTASI BELAJAR SEJARAH INDONESIA - Wita Yulistia; Taufik Taufik (Herodotus: Jurnal Pendidikan IPS, 2019)
The purpose of this study was to determine how much influence of learning interest and independent learning on learning achievement of Indonesia History at state vocational school students in Bogor Regency. The research method used in this study is a survey method with correlation analysis. While the data and information in the field is captured with the help of a questionnaire. Based on data analysis, it can be concluded that: (1) There is a significant influence of learning interest and independent learning on learning achievement of Indonesia History at state vocational school students in Bogor Regency. It was proven by the acquisition of Sig = 0,000 <0.05 and Fcount = 46.992. (2) There is a significant influence of learning interest and independent learning on learning achievement of Indonesia History at state vocational school students in Bogor Regency. It is was proven by the acquisition of Sig = 0,000 <0.05 and tcount= 3.988. (3) There is a significant influence  of learning interest and independent learning on learning achievement of Indonesia History at state vocational school students in Bogor Regency. It was proven by the acquisition of Sig = 0,000 <0.05 and tcount= 5.739.